Clawback Sukuk as Contingent Capital for Islamic Banks: An Empirical Analysis - Kenneth Nolan Daniels (Department of Sharia Financial Management, Institut Agama Islam Negeri Sultan Amai Gorontalo, Indonesia, 2026)
We extend the contingent capital framework of clawback bonds to Islamic banks under Shariah law. Using panel data on 20 major Islamic and conventional banks from 2015-2024 with 61 sukuk issuances, we find that clawback provisions reduce funding costs by 46 basis points for Islamic banks compared to only 13 basis points for conventional banks—an additional benefit of 33 basis points. This differential effectiveness stems from the natural alignment between clawback mechanisms and profit-sharing principles inherent in Islamic finance. We identify an optimal trigger level of 10-12% CET1 for Islamic banks, higher than the 7-9% optimal for conventional banks, reflecting Islamic banks' higher baseline capital ratios and lower leverage. Our findings suggest clawback sukuk should be prioritized as Shariah-compliant contingent capital instruments, offering superior loss-absorption characteristics while maintaining regulatory compliance with IFSB standards.